Two new Erythrobasidium species inhabiting the phyllosphere discovered in the Baotianman Nature Reserve in China - Lu, Yun-Feng; Chai, Chun-Yue; Hui, Feng-Li (Frontiers in Microbiology, 2024)
The genus Erythrobasidium is kind of species-scarce and undersampling basidiomycetes. Currently, only six species have been accepted into the genus and the diversity still remains incompletely understood. In this study, five Erythrobasidium strains were isolated in the surface of plant leaves collected from the Baotianman Nature Reserve, Henan Province, central China. Phylogenetic analyses of the small ribosomal subunit (SSU) rRNA gene, the internal transcribed spacer (ITS) region, the D1/D2 domain of the large subunit (LSU) rRNA gene, and the translation elongation factor 1-α (TEF1-α) gene coupled with morphological studies were employed to characterize and identify these isolates. As a result of these, two new species, namely E. turpiniae sp. nov. and E. nanyangense sp. nov., were delimited and proposed based on morphological and molecular evidence. A detailed description and illustration of both new species, as well as their differences with the close relatives in the genus are provided. An identification key for Erythrobasidium species is also provided. This study provides further insights into our understanding of Erythrobasidium species.